Survival and fertility of bitches undergoing caesarean section. (3rd October 2019) - Conze, Theresa; Jurczak, Andrzej; Fux, Vanessa; Socha, Piotr; Wehrend, Axel; Janowski, Tomasz
Abstract : Background: With the increasing popularity of planned caesarean section, the need for knowledge regarding this surgery has become increasingly important. The reported death and survival rates for caesarean sections vary widely. Another important aspect is the fertility rate in subsequent oestrous after caesarean section. The aim of this study was to investigate the mortality and survival rate of bitches during caesarean section. Additionally, the fertility of bitches after caesarean sections was determined. Methods: Caesarean sections which were performed in the years 1997–2009 at two university clinics were evaluated retrospectively. A distinction was made between bitches in which a conservative caesarean section was performed and bitches with a caesarean section followed by an ovariohysterectomy. Results: A total of 482 caesarean sections were included in the study. The overall mortality rate was 3.11 per cent, with 2.59 per cent during or after a conservative caesarean section and 4.19 per cent during or after caesarean section with ovariohysterectomy. The reason for ovariohysterectomy was the owner's preference in 63 bitches (47.01 per cent); in 71 (52.98 per cent) bitches, ovariohysterectomy was performed due to a medical indication. The fertility rate after caesarean section was 100 per cent. Conclusion: The results show a high mortality rate during and after caesarean section. On the other hand, caesarean section does not seem to have a big impact on further fertility. Further studies are needed to investigate possible reduction of litter sizes and the suitability of caesarean section in subsequent pregnancies.